2005
DOI: 10.1074/jbc.m413610200
|View full text |Cite
|
Sign up to set email alerts
|

Locating an Antagonist in the 5-HT3 Receptor Binding Site Using Modeling and Radioligand Binding

Abstract: We have used a homology model of the extracellular domain of the 5-HT 3 receptor to dock granisetron, a 5-HT 3 receptor antagonist, into the binding site using AUTODOCK. This yielded 13 alternative energetically favorable models. The models fell into 3 groups. In model type A the aromatic rings of granisetron were between Trp-90 and Phe-226 and its azabicyclic ring was between Trp-183 and Tyr-234, in model type B this orientation was reversed, and in model type C the aromatic rings were between Asp-229 and Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
119
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(137 citation statements)
references
References 40 publications
16
119
0
2
Order By: Relevance
“…Residues were mostly mutated to amino acids with similar chemical properties to prevent complications arising from changes in channel gating. Conserva- tive changes minimize the impact on receptor structure and function, but still reveal specific interactions between the receptor and antagonist (e.g., Thompson et al, 2005). Wildtype and mutant receptors (except for S2ЈT and S12ЈT, which were nonfunctional) responded to 5-HT in a concentrationdependent manner, with EC 50 and n H values of mutants differing Ͻ6-fold from wild type (Table 1; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Residues were mostly mutated to amino acids with similar chemical properties to prevent complications arising from changes in channel gating. Conserva- tive changes minimize the impact on receptor structure and function, but still reveal specific interactions between the receptor and antagonist (e.g., Thompson et al, 2005). Wildtype and mutant receptors (except for S2ЈT and S12ЈT, which were nonfunctional) responded to 5-HT in a concentrationdependent manner, with EC 50 and n H values of mutants differing Ͻ6-fold from wild type (Table 1; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This was performed as described previously (Reeves et al, 2003;Thompson et al, 2005). Three-dimensional models of the extracellular region of the glycine receptor were built using MODELLER 6, version 2 (http://salilab.org/modeller/) based on the crystal structure of acetylcholine-binding protein in the agonistbound state (carbamylcholine; Protein Data Bank ID 1UV6).…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been made possible by the availability of the high resolution structure of the acetylcholine binding protein (AChBP), which is homologous to the extracellular domain of the nicotinic ACh receptor (6). Using this as a template, computer-generated models of ligandbinding pockets of Cys loop receptors, combined with previous data from structure-activity studies, have identified important features of these pockets and on the orientation of agonists and antagonists when located in their binding sites (7)(8)(9)(10)(11)(12)(13). Generating an accurate representation of the orientation of GABA in the GABA C receptor-binding site could identify the processes involved in ligand recognition at this receptor and would also assist in drug design; current data indicate that drugs acting on GABA C receptors could possibly be used to treat visual, sleep, and cognitive disorders (4,14).…”
Section: Gabamentioning
confidence: 99%